Intervention of NF-Κb Signaling Pathway and Preventing Post-Operative Cognitive Dysfunction as Well as Neuronal Apoptosis - Na Yuan; Xiuzhen Wang; Yu Zhang; Lingsi Kong; Liyong Yuan; Yeying Ge (Tehran University of Medical Sciences, 2022)
Background: The Postoperative cognitive dysfunction (POCD) model was constructed by resection of the left hepatic lobe in aged mice to determine the behavioral effects of the POCD model in aged mice and the relationship between NF-κB and POCD in apoptosis and autophagy. Provide a theoretical basis for POCD prevention and treatment. Methods: This study was carried out in Ningbo No. 6 Hospital, Zhejiang, China, from Jun 2019 to Dec 2020. The POCD model was constructed after resection of the left extrahepatic lobe in aged mice and randomly divided into 6 groups: sham operation group, operation group (normal saline control group, solvent group, YC-1 group, PDTC group and 3-MA group). Related indicators of behavioral changes, neuronal inflammatory responses, apoptosis, and autophagy were examined. Results: The escape latency of the aged mice in the surgical group was significantly prolonged at three time points compared with the control group, and the number of insertions decreased significantly. Microglia are activated and the inflammatory response is increased, whereas PDTC has an inhibitory effect. It was demonstrated that apoptosis and necrosis of neurons can be induced by the NF-κb pathway, and autophagy can be promoted, whereas autophagy occurs before apoptosis. Conclusion: Activation of NF-κb pathway in neurons after POCD causes neuronal apoptosis and autophagy, and cognitive impairment occurs. PDTC, a NF-κb pathway inhibitor, can effectively reduce neuronal apoptosis induced by secondary brain injury after POCD. Necrosis, to protect the brain tissue.